2016
DOI: 10.3389/fnbeh.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Hoarders Only Discount Consumables and Are More Patient for Money

Abstract: Individuals with hoarding disorder (HD) excessively acquire and retain goods while also exhibiting characteristics of impulsivity and addiction. However, HD individuals do not always perform impulsively in experiments, they do not appear interested in money, and they exhibit many features of risk-aversion and future-planning. To examine impulsivity in HD, we compared validated community participants high and low in hoarding tendencies on questionnaire measures of hoarding and impulsivity as well as a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…This finding contributes to disconfirm the impulsivity-based pathogenesis for HD while suggesting a future planning prompting aim. Hence, hoarders do not always show the typical features of those psychopathological conditions that have been traditionally investigated and treated by focusing on impulsivity/impulse control, such as short-sighted decision making (Vickers et al, 2016 ). For example, Vickers et al ( 2016 ) reported that hoarders, compared to non-hoarders, were more impulsive (more impatient) for consumables rather than for money, as measured through a temporal (or delay) discounting task.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding contributes to disconfirm the impulsivity-based pathogenesis for HD while suggesting a future planning prompting aim. Hence, hoarders do not always show the typical features of those psychopathological conditions that have been traditionally investigated and treated by focusing on impulsivity/impulse control, such as short-sighted decision making (Vickers et al, 2016 ). For example, Vickers et al ( 2016 ) reported that hoarders, compared to non-hoarders, were more impulsive (more impatient) for consumables rather than for money, as measured through a temporal (or delay) discounting task.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, hoarders do not always show the typical features of those psychopathological conditions that have been traditionally investigated and treated by focusing on impulsivity/impulse control, such as short-sighted decision making (Vickers et al, 2016 ). For example, Vickers et al ( 2016 ) reported that hoarders, compared to non-hoarders, were more impulsive (more impatient) for consumables rather than for money, as measured through a temporal (or delay) discounting task. Temporal discounting is a cognitive phenomenon defined as the progressive decline in the subjective value of a given reward as the time of its receipt is delayed in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that HD represents the extreme end of a continuum that includes typical endowment processes lower down on the spectrum, since hoarding is an adaptive process that exists across species, exists across people on a spectrum, and exhibits similar psychopathological and behavioral patterns in control and HD participants ( Frost et al, 1995 ; An et al, 2009 ; Preston et al, 2009 ; Norberg et al, 2015 ; Vickers et al, 2016 ). Further, many HD studies have successfully demonstrated hoarding-related issues using non-clinical participants ( Preston et al, 2009 ; Tolin et al, 2009 , 2012 ; Wang et al, 2012 ; Norberg et al, 2015 ; Shaw et al, 2015 ; Vickers et al, 2016 ). Because hoarding exists on a continuum, and this study includes non-clinical participants, hoarding symptom scores are referred to hereafter as “tendencies” so as not to imply that participant scores necessarily represent a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover hoarding-related phenomena have been observed in non-patients previously and exist on a continuum. In addition, the use of a food item was expected to work because individual differences in hoarding tendencies previously correlated with intertemporal discounting for snack foods, even when identical items were offered to participants in large quantities ( Vickers et al, 2016 ). Food also activates the decision and reward system that motivates organisms toward valued items ( Chib et al, 2009 )—regions that support decisions about goods and that correlate with hoarding tendencies ( Preston, 2013a ).…”
Section: Introductionmentioning
confidence: 99%